The Determinants of Rural Household Food Consumption Expenditure in Lesotho: Impact of Off-farm Income - Ernest Ngeh Tingum; Ademola Kuponiyi (Journal of Social and Development Sciences, 2020)
Most smallholder farmers in Sub-Saharan African need to diversify into nonfarm/off-farm income generating activities in order to ensure household food security through optimum consumption expenditure. The aim of this study was to investigate the effect of off-farm income on rural household food consumption expenditure in Lesotho, using secondary data from a comprehensive and representative Household Budget Survey of 2017. The survey design for data collection adopted a two stage stratified sampling procedure. The analysis used two econometric models. The OLS regressions were employed to identify important determinants of household food consumption expenditure and Instrumental Variable (IV) approach was employed to account for endogeneity issues. The results revealed a consistent positive and significant effect of off-farm income on household food consumption expenditure across all models. Household size, transfers and remittances were found to increase household food consumption expenditure significantly and positively. Government is advised to encourage and improve conditions under which rural smallholder farmers could participate in off-farm income generating activities.